Socialization of Business Creation and Utilizing Social Media as a Product Marketing Strategy at Perum Kopti, East Jakarta - Darmeinis, Darmeinis; Siahaan, Leroy Holman; Agustina, Silvia; Prasetyo, Reinaldo; Ardyaputri, Syafa Kamila; Budiarti, Rizka Wahyu; Wulandari, Yayang; Saputra, Feri Ragil (Jurnal Pengabdian Masyarakat Formosa, 2024)
One of these obligations as a student of Panca Sakti University Bekasi will carry out Community Service, this is carried out in connection with concerns about following technological developments and advances, especially Indonesia as a country that has a lot of natural and human resource potential that cannot be equated with developed countries. this concern is by organizing Community Service activities in the form of "Socialization of Business Making And Using Social Media As A Product Marketing Strategy For Young People In Perum Kopti" The method of activity carried out is using presentation sessions to convey basic information about marketing strategies through social media. Followed by a discussion session to provide space for participants to ask questions, share experiences, and collaborate.